Intravenous tranexamic acid for hyperacute primary intracerebral hemorrhage: Protocol for a randomized, placebo-controlled trial. Issue 6 (August 2016) - Sprigg, Nikola; Robson, Katie; Bath, Philip; Dineen, Robert; Roberts, Ian; Robinson, Tom; Roffe, Christine; Werring, David; Al-Shahi Salman, Rustam; Pocock, Stuart; Duley, Lelia; England, Tim; et al.
Rationale: Outcome after intracerebral hemorrhage remains poor. Tranexamic acid is easy to administer, readily available, inexpensive, and effective in other hemorrhagic conditions. Aim: This randomized trial aims to test the hypothesis that intravenous tranexamic acid given within 8 h of spontaneous intracerebral hemorrhage reduces death or dependency. Design: Phase III prospective double-blind randomized placebo-controlled trial. Participants within 8 h of spontaneous intracerebral hemorrhage are randomized to receive either intravenous tranexamic acid 1 g 10 min bolus followed by 1 g 8 h infusion, or placebo. Sample size estimates: A trial of 2000 participants (300 from start-up phase and 1700 from main phase) will have 90% power to detect an ordinal shift of the modified Rankin Scale with odds ratio 0.79. Study outcomes: The primary outcome is death or dependency measured by ordinal shift analysis of the 7 level mRS at day 90. Secondary outcomes are neurological impairment at day 7 and disability, quality of life, cognition, and mood at day 90. Safety outcomes are death, serious adverse events, thromboembolic events, and seizures. Cost outcomes are length of stay in hospital, readmission, and institutionalization. Discussion: This pragmatic trial is assessing efficacy of tranexamic acid after spontaneous intracerebral hemorrhage. Recruitment started in 2013; as of 15th January 2016 1355 participants have been enrolled, from 95 centers in seven countries. Recruitment is due to end in 2017. TICH-2 Trial is registered as ISRCTN93732214.